Groupactivities and enhancement of oral proficiency of the management and commerce students in english as a second language [esl] classroom - JoeInparaj, C.T. (University of Jaffna, 2016)
The process of Teaching-Learning in higher education stream is now changing. Active student-centered learning has become a vital focus in modern pedagogical trend. Therefore this research was undertaken to bridge the gap between teaching theories and practices to make ESL teaching most effective. Globalization has opened new avenues and increased the opportunity for international achievements. ESL teachers are expected to mould their students as enthusiastic communicators in the globalized world. Interaction has considerable influence on second language learning. Group work promotes collaboration among learners and it leads to peer-scaffolding. Since speaking is the primary productive skill, this study is limited to the competency level of oral proficiency. Objective of this study was to examine and identify the students' perspectives with regard to their involvement in group activities to develop their oral proficiency in English. To achieve this objective, data were collected through the analysis of questionnaires, interviews as well as observations during the teaching-learning process of the first year students of the Faculty of Management studies and Commerce. The respondents of this study consist of fifty students from commerce and fifty students from management. A quantitative analytical comparative methodology was utilized. Findings of this study brought out the factors which hinder students' participation in speaking activities and confirmed that well-planned group activity is the corner-stone to build-up confidence among themselves to achieve their target competency level in speaking skill
Keywords: ESL classroom; Group activity; Interaction; Oral proficiency